2012
DOI: 10.4103/2230-8210.105575
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in pediatrics: A hormone from adipocyte that wheels several functions in children

Abstract: The protein leptin, a pleiotropic hormone regulates appetite and energy balance of the body and plays important roles in controlling linear growth, pubertal development, cardiovascular function, and immunity. Recent findings in the understanding of the structure, functional roles, and clinical significance of conditions with increased and decreased leptin secretion are summarized. Balance between leptin and other hormones is significantly regulated by nutritional status. This balance influences many organ syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 81 publications
4
31
1
1
Order By: Relevance
“…It stimulates the width of the proliferative zone of the epiphyseal growth plate and increases the expression of chondroitin sulfate within the cartilaginous matrix. Apparently, leptin acts as a direct skeletal growth factor in children [40]. This effect of leptin is in concordance with our result revealing the higher serum leptin levels in the children with taller body height.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It stimulates the width of the proliferative zone of the epiphyseal growth plate and increases the expression of chondroitin sulfate within the cartilaginous matrix. Apparently, leptin acts as a direct skeletal growth factor in children [40]. This effect of leptin is in concordance with our result revealing the higher serum leptin levels in the children with taller body height.…”
Section: Discussionsupporting
confidence: 93%
“…Apparently, leptin acts as a direct skeletal growth factor in children [40]. It stimulates the width of the proliferative zone of the epiphyseal growth plate and increases the expression of chondroitin sulfate within the cartilaginous matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is one of several key signals that control food intake and energy balance, with multiple functions through receptors located centrally and peripherally (26,27). Recent studies have found that the exogenous adipokines (including leptin) contribute to changes in GnRH pulse release by binding to leptin receptors in the hypothalamus (28). In subjects with increased levels of leptin, GnRH pulse release started to increase in frequency and promote the onset of puberty (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors have been shown to play a role in the development of these diseases, such as eating disorders [3][4][5], chronic distress [6] and hormonal imbalances [7]. Apart from their origins, the increase in overweight and obesity is of particular concern as they are linked to numerous chronic diseases and other health disorders among both adults [8] and children [9][10][11].…”
Section: Introductionmentioning
confidence: 99%